Alunos surdos-alunos ouvintes : uma análise dialógica de momentos interacionais - Almeida, Sérgio Henrique de Souza (2014)
This research focuses on the interactions between deaf students and their non-deaf classmates, analyzing communicative aspects observed in the social interactions in EMEB Maria da Glória de Souza, in Cuiabá. The entire research sought to understand how deaf students and non-deaf students interact, through the language, in school. Therefore, our overall objective was to observe whether there is interaction between deaf students and non-deaf students in the school environment, since, in Mato Grosso, there are no studies that analyze the issue of the deaf-non-deaf student interaction under a Bakhtinian perspective. We believe that the concept of interaction, widespread in the school sphere, requires a better understanding and reframing, taking into account our theoretical and methodological framework. In an attempt to base our theoretical positions, we will seek to bring as a contribution to the field of linguistic studies, a more clarified distinction of how social interaction is conceived in the studies of Mikhail Bakhtin and Levy Vygotsky. In this direction, we understand, in this study, the language as a place of human interaction, a social phenomenon, historical and ideological, as well as defined by Bakhtin/Volochínov (2012 [1929]); allies itself with the context of researches on the teaching that presents itself today, in which it’s presumed a non individual, nor a-historical consideration of the processes of teaching and learning. These studies have in common the adoption of the socio-historical learning theory of Vygotsky (1930), coupled with the enunciation-discursive perspective of Bakhtin and the Circle (1929; 1953), relying on several of its notions, especially regarding interaction, dialogical relations, dialogue, otherness, exotopy, sign, concrete statement, active understanding. The theoretical-methodological approach used in the research was the qualitative approach, and the dialogical analysis based on Brait (2006) and Amorim (2001), watching interactive moments, registered in a historical-cultural and semiotic interpretation of the processes of human interaction. Six classes were observed and filmed in the selected school’s 6th year, during March and April of 2014. The results of our analysis indicate that linguistic and cultural differences have not prevented social interaction between deaf students and non-deaf students. We note that this occurs in the realization of all group activities proposed in the classroom. It became evident to us that, for children, the inclusion is much more natural than for the adults present at school environment. The experience of inclusion proves to be beneficial for deaf students and non-deaf students, as they can better develop their concepts about deafness, sign language and the deaf community, developing themselves as not indifferent citizens.